THE RELATIONSHIP BETWEEN THE STAGE OF NASOPHARYNGEAL CARCINOMA WITH ANEMIA AND NUTRITIONAL STATUS IN WEST NUSA TENGGARA GENERAL HOSPITAL - Ni Ketut Susilawati; Hamsu Kadriyan; Wayan Putu Sutirtayasa (INTERNATIONAL JOURNAL OF NASOPHARYNGEAL CARCINOMA, 2020)
Introduction: Nasopharyngeal carcinoma is the most common malignant tumor in the ENT-HNS were the highest of all malignant tumors of the head and neck. Malnutrition and cachexia is a common problem in cancer patients and impact on quality of life and survival. Anemia is a major problem in patients with nasopharyngeal cancer receiving chemotherapy or radiotherapy. Objective: Determine the relationship of nasopharyngeal carcinoma stage with anemia and nutritional status. Material and methods: This study used cross sectional analytic method. Data were obtained from medical records of patients with nasopharyngeal carcinoma who were treated in province hospital West Nusa Tenggara period January 2018 to December 2018. Data collected include the identity, diagnosis, hemoglobin value, weight and height. Having analyzed the data collected are looking for is there a relationship between stage nasopharyngeal carcinoma with anemia and nutritional status. Results: In this study, Shapiro-Wilk normality test. Anova is then performed to analyze the relationship stage nasopharyngeal carcinoma with anemia status obtained 95% CI, p value 0.847, there is no difference between stage nasopharyngeal carcinoma with anemia. Kruskal Wallis test to analyze the relationship with BMI (body mass index) with stage nasopharyngeal carcinoma obtained 95% CI, p value 0.565. There is no difference in BMI with stage nasopharyngeal carcinoma. Conclusion: There is a tendency to lower Hb in patients with nasopharyngeal cancer further stage although there is no significant difference between each stage. The same thing was found in BMI, BMI decreased tendency in patients with advanced nasopharyngeal cancer although there was no statistically significant difference.